Governing the banking industry: A severe case of supervisory failure - Martín Lagos (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2013)
After summarizing the birth and basic notions of credit, money and banking, sections 1 to 4 review the extraordinary potential, but also the substantial core risks of fractional reserve banking. The appearance of central banks, fiduciary monies, prudential regulation and supervision, as well as technological change, had huge impact on banking, but its basic business model remained the same old, risky one. Sections 5 and 6 describe how the contagion risk proper of the opaqueness and informational asymmetries of commercial banking plus the external diseconomies associated to systemic crises have justified the growth of thick safety nets, guarantees and government involvement in critical situations. These realities require not only top-level technical expertise in the supervisory bodies, but also outstanding moral integrity and political independence within their heads. Sections 7 and 8 pretend to summarize the key factors surrounding the subprime mortgage lending bubble and the supervisory failure leading to the worst economic crisis in seventy years.
Keywords: 330; Bank; Bankenaufsicht